The hydrology of treed wetlands in thawing discontinuous permafrost regions. Issue 5 (21st April 2021) - Disher, Brenden S.; Connon, Ryan F.; Haynes, Kristine M.; Hopkinson, Christopher; Quinton, William L.
Abstract: In peatland‐dominated regions of discontinuous permafrost, widespread permafrost thaw has led to an expansion of treed wetlands on the landscape. Treed wetlands have greater topographic variation than the collapse scar wetlands from which they evolved, but their hydrological role in the landscape has not been identified. This study examines the development of treed wetlands, and characterises their physical, thermal and hydrological properties in relation to their adjacent peat plateaus and collapse scar wetlands. Electrical resistivity tomography was used to determine the geophysical characteristics of treed wetlands. Snow cover, soil moisture and temperature, as well as water level and storm response were monitored and compared in treed wetlands, plateaus and collapse scars. Treed wetlands were permafrost free, although unlike collapse scars they may contain multi‐year ice bulbs. For treed wetlands, the late‐winter snow water equivalent, average soil temperature and moisture, unsaturated layer thickness and duration of frozen ground were all intermediate between those of peat plateaus and collapse scars. Treed wetlands interact hydrologically with adjacent peat plateaus and collapse scars in one of two types of local flow sequences depending upon topographic position, which governs the potential role of treed wetlands as a thermal buffer if treed wetlands are situated between a collapse scar wetland and permafrost‐cored peat plateau. As permafrost thaw reduces the cover of both peat plateaus and the collapse scar wetlands that develop from them, the development and expansion of treed wetlands appear to be transitioning plateau‐wetland complexes into the permafrost‐free black spruce forest.